Exercise reward induces appetitive 50-kHz calls in rats - Heyse, Natalie C. (2015)
Rats express affective states by visible behaviors (like approach or flight) and through different kinds of ultrasonic vocalizations (USV). 50-kHz calls are thought to reflect positive affective states since they occur during rewarding situations like social play or palatable food. However, the effects of voluntary exercise on USV have not been investigated yet, although such exercise can serve as reward. To this aim, we gave young adult rats restricted daily access to a runway maze, where they could interact with either a movable (experimental group) or locked wheel (sedentary group) for 14 days and we tested USV in anticipation of and during subsequent running. We also studied inter-individual differences in running, and relationships with USV, and rat-typical trait measures. The results showed that the experimental rats had to be separated into “runners” and “pseudorunners” since only runners performed true running, whereas pseudorunners hardly entered the wheel and turned it only with their forelimbs. This outcome seems to be related to subject-dependent differences in responding to novelty and in reward sensitivity, as indicated by pertinent screening tests, which we had performed prior to the 14 days of wheel access. In the runway, our experimental and control groups did not differ in visible anticipatory behavior, like approach. Yet, only runners and sedentary rats displayed an increasing but similar amount of anticipatory USV, which is suggestive of a state of incentive anticipation of the coming wheel access. During exercise, only runners increased USV, probably indicating a highly positive emotional state. To conclude, voluntary exercise provides a promising tool to induce 50-kHz USV during and in anticipation of exercise. When performing such studies, possible individual differences between subjects have to be taken into account, and the actual wheel performance should carefully be controlled.